1987
DOI: 10.1210/endo-120-4-1503
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gonadotropin-Releasing Hormone and Estradiol on Luteinizing Hormone Biosynthesis in Cultured Rat Anterior Pituitary Cells*

Abstract: This study investigated the effects of physiological concentrations of GnRH and estradiol (E2) on LH biosynthesis and release using cultured anterior pituitary cells. Pituitaries from female rats were enzymatically dispersed and cultured for 48 h in steroid-free alpha-Modified Eagle's Medium, followed by a 24-h culture in medium with or without E2. The cells were then incubated for a 4-h (Exp 1 and 2) or 8-h (Exp 3) period in medium containing radiolabeled precursors with or without GnRH. Radioactive precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
42
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 43 publications
6
42
0
3
Order By: Relevance
“…Results showed that while progesterone by itself had no effect (control groups), saturation of PR with the cognate ligand reversed the inhibitory effect of attenuin on LH protein levels, although not on LH secretion (Gordon et al, 2010b). Apart from these results showing that attenuin probably inhibits LH synthesis at post-transcriptional level, little is known about the mechanism involved in that inhibition -probably by increasing LH degradation (Kitahara et al, 1990) and/or decreasing GnRH-induced LH polypeptide glycosylation (Ramey et al, 1987) except that, as indicated earlier, the inhibitory pathway in LH synthesis involves the gonadotrope PR. However, the detailed mechanism underlying the PR-mediated attenuininduced inhibition of LH protein levels requires further detailed investigation.…”
Section: The Relationship Between Attenuin Pr and Lh Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that while progesterone by itself had no effect (control groups), saturation of PR with the cognate ligand reversed the inhibitory effect of attenuin on LH protein levels, although not on LH secretion (Gordon et al, 2010b). Apart from these results showing that attenuin probably inhibits LH synthesis at post-transcriptional level, little is known about the mechanism involved in that inhibition -probably by increasing LH degradation (Kitahara et al, 1990) and/or decreasing GnRH-induced LH polypeptide glycosylation (Ramey et al, 1987) except that, as indicated earlier, the inhibitory pathway in LH synthesis involves the gonadotrope PR. However, the detailed mechanism underlying the PR-mediated attenuininduced inhibition of LH protein levels requires further detailed investigation.…”
Section: The Relationship Between Attenuin Pr and Lh Synthesismentioning
confidence: 99%
“…The preovulatory secretion of LH is the result not only of increased LH synthesis (Tse et al, 1993) but also of increased LH secretion by gonadotropes (Ramey et al, 1987). While the effects of attenuin on LH secretion have been exhaustively studied, it is not known whether attenuin has any effect on LH synthesis.…”
Section: The Relationship Between Attenuin and Lh Synthesismentioning
confidence: 99%
“…The direct effects have been extensively studied in primary cultures of rat pituitary cells in which oestradiol can amplify GnRH-stimulated gonadotrophin secretion (Tang et al 1982) and can increase GnRH receptor number (Clayton 1989) and influence gonadotrophin subunit expression (Ramey et al 1987, Phillips et al 1988. In terms of GnRH signalling, oestradiol has been shown to influence the Ca 2+ response to GnRH (Leong & Thorner 1991) and the effects of GnRH on Ca 2+ mobilisation and Ins(1,4,5)P 3 generation are increased in cells from pro-oestrous rats and reduced in those from ovariectomised rats (Mitchell et al 1988).…”
mentioning
confidence: 99%
“…Στην παρούσα µελέτη, µία παρόµοια αύξηση στις συγκεντρώσεις της Ε2 στον ορό βρέθηκε στις φυσιολογικές και στις γυναίκες µε PCOS. Αυτό το στεροειδές ευαισθητοποιεί την υπόφυση στη GnRH για την παραγωγή γοναδοτροφινών µέσω πολλαπλών µηχανισµών, συµπεριλαµβανοµένης και της αύξησης του αριθµού των υποδοχέων της GnRH (self-priming effect) (Ramey et al, 1987;Danforth et al, 1990;Laws et al, 1990).…”
Section: συζητησηunclassified
“…Έχει βρεθεί ότι η βραχυπρόθεσµη (<12 ώρες) έκθεση των καλλιεργηµένων υποφυσιακών κυττάρων στην Ε2 αυξάνει τον αριθµό των υποδοχέων της GnRH (Gregg et al, 1990) και την από τη GnRH προκαλούµενη έκκριση της LH (Huang and Miller, 1980). Η µακροπρόθεσµη (24-48 ώρες) in vitro έκθεση των γοναδοτρόφων του επίµυος (Speight and Fink, 1981b) ή του προβάτου (Fowler et al, 1992(Fowler et al, , 1993) στην Ε2 έχει µικρή επίδραση στην έκκριση της LH από τη GnRH, αν και η συνεχής έκθεση στην Ε2 κατά τη διάρκεια µίας πρόκλησης µε GnRH ενισχύει την από τη GnRH προκαλούµενη σύνθεση και έκκριση της LH (Ramey et al, 1987). Εχει προταθεί ότι η αυξηµένη στον ορό LH που παρατηρείται περίπου στο 40% των ασθενών µε PCOS σχετίζεται µε τη συνεχή θετική δράση της Ε2 στην υπόφυση (Lobo et al, 1981;Waldstreicher et al, 1988).…”
Section: συζητησηunclassified